Einstein the class hamster - Tashjian, Janet (Christy Ottaviano Books, Henry Holt and Company, 2013)
Einstein, a very knowledgeable hamster, is desperate to help the students in his classroom win an audition for a televised trivia game show but, unfortunately, only one student, Ned, can hear him.